2021
DOI: 10.1080/07853890.2021.1921838
|View full text |Cite
|
Sign up to set email alerts
|

Effects of data preprocessing on results of the epidemiological analysis of coronary heart disease and behaviour-related risk factors

Abstract: Tuomainen (2021) Effects of data preprocessing on results of the epidemiological analysis of coronary heart disease and behaviour-related risk factors,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 29 publications
(33 reference statements)
1
11
0
Order By: Relevance
“…In this study, we used the fasting serum low-density lipoprotein cholesterol (S-LDL-C) concentration instead of the fasting serum total cholesterol (STC) concentration to detect high cholesterol levels. In our previous paper, we had used STC [ 26 ], but preliminary analyses of this study revealed that S-LDL-C could provide even stronger associations with CHD. Based on S-LDL-C concentration we categorised study participants as follows: S-LDL-C < 3.4 mmol/L indicating below borderline concentrations, S-LDL-C 3.4 − 4.1 mmol/L indicating borderline high concentrations, and S-LDL-C > 4.1 mmol/L or cholesterol-lowering medication indicating high concentrations.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…In this study, we used the fasting serum low-density lipoprotein cholesterol (S-LDL-C) concentration instead of the fasting serum total cholesterol (STC) concentration to detect high cholesterol levels. In our previous paper, we had used STC [ 26 ], but preliminary analyses of this study revealed that S-LDL-C could provide even stronger associations with CHD. Based on S-LDL-C concentration we categorised study participants as follows: S-LDL-C < 3.4 mmol/L indicating below borderline concentrations, S-LDL-C 3.4 − 4.1 mmol/L indicating borderline high concentrations, and S-LDL-C > 4.1 mmol/L or cholesterol-lowering medication indicating high concentrations.…”
Section: Methodsmentioning
confidence: 99%
“…We also excluded measures of physical activity since the proportion of physically inactive men in the KIHD cohort is practically zero and, consequently, it is impossible to estimate the impact of sedentary lifestyle on the risk of CHD. Moreover, based on our previous analyses physical activity levels very poorly predict the risk of CHD in this cohort [ 26 ]. Other studies also have found the contradictory nature of physical activity, as in some study populations physical activity, not inactivity, is associated with an increased risk of CHD [ 9 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations